Thunau am Kamp - das frühmittelalterliche Gräberfeld auf der Oberen Holzwiese - Nowotny, Elisabeth (Mitteilungen der Prähistorischen Kommission der Österreichischen Akademie der Wissenschaften ;, 2018)
The burial ground on the Obere Holzwiese consists of 215 burials and is therefore by far the largest uncovered burial site of Carolingian times in Lower Austria north of the Danube. It belonged to a fortified central settlement, a center of power, the core of which built a 'manor farm'. In addition to the comprehensive archaeological analysis the volume contains investigations concerning archaeobotanics, material analyses, metallography, anthropology, textiles and leather.